The Role of Platelets in the Pathogenesis of Thrombosis and Hemorrhage in Patients with Thrombocytosis - Walsh, Peter N.; Murphy, Scott; Barry, William E. (Thrombosis and Haemostasis, 1977)
Some patients with thrombocytosis due to myeloproliferative diseases or other etiologies experience thromboembolic complications and others may bleed excessively. It seems unlikely that elevations in platelet count per se are a direct cause either of thrombosis or of hemorrhage. In an effort to ascertain whether variations in platelet function might determine whether an individual patient experiences thrombotic or hemorrhagic complications we have evaluated platelet function in 22patients with thrombocytosis due to a variety of etiologies. The results of platelet counts, bleeding time determinations, and studies of platelet aggregation were similar in patients with thrombosis, in patients with bleeding and in patients with neither complication. Therefore, detailed studies of platelet coagulant activities were carried out in 8patients. The results of platelet coagulant activity assays were normal in all 3patients with thrombocytosis and neither thrombotic nor bleeding complications and an additional 3patients with myeloproliferative diseases, normal platelet counts and no thrombohemorrhagic complications. In 2patients with thrombotic complications significant elevation of platelet coagulant activities concerned with the early phases of intrinsic coagulation were observed whereas in 2patients with severe hemorrhagic complications deficiences of either contact forming activity or collagen-induced coagulant activities were evident. This preliminary study suggests the possibility that variations in platelet coagulant activities concerned with the early stages of intrinsic coagulation may determine whether patients with thrombocytosis will experience bleeding or thrombotic complications.